Effect of aqueous extracts of quinoa mojuelo (Chenopodium quinoa Willd.) on arupo plants (Chionanthus pubescens Kunth) - Castro-Albán, Hugo Alejandro; Castro-Gómez, Rosa del Pilar; Alvarado-Capó, Yelenys; Guanga-Chunata, Deysi Margoth; Núñez-Torres, Darwin Alberto; Montenegro-Robalino, Víctor Hugo (Agronomía Mesoamericana, 2025)
Introduction. Chionanthus pubescens Kunth is an endemic tree of southern Ecuador with ornamental uses due to its pink inflorescence in the villages of the region. Objective. To evaluate the effect of aqueous extracts of quinoa mojuelo on the growth of arupo plants (Chionanthus pubescens Kunth) and the incidence of Fusarium sp. Materials and methods. The test was carried out in the province of Chimborazo, Ecuador, during the year 2022.The aqueous extracts of quinoa mullein were obtained using the Soxhlet method, and their concentrations were determined by UV-VIS spectrophotometry. A completely randomized block design with a bifactor arrangement was used, with three levels for factor A (aqueous extract of mojuelo: mother extract (100 %), diluted 50 %, 75 % in sterile distilled water; v/v, and three levels for factor B, (frequency of application: every 7, 14 and 21 days), in total ten treatments (including an absolute control) with three repetitions each. They were evaluated in ten plants selected at random by treatment the morphological variables (height, number of leaves per plant and stem diameter), as well as the incidence of Fusarium sp. Results. The results showed that the concentrations of 50 and 75 % aqueous extract of mojuelo, applied weekly, achieved the best morphological development and the lowest percentage of affectation by Fusarium sp. in arupo (C. pubescens) plants, reflected in the height (16.3 cm), number of leaves (17.8), stem diameter (6.5 cm) and the incidence of the disease (50 %). Conclusions. The aqueous extracts obtained from quinoa mojuelo (Chenopodium quinoa Willd.) applied to arupo plants (Chionanthus pubescens Kunth) in the nursery, reduce the incidence of Fusarium wilt and promote growth in the first stages of development.